Put Your Money Where Your Butt Is : A Commitment Contract for Smoking Cessation - Giné, Xavier; Karlan, Dean; Zinman, Jonathan (2012)
The authors designed and tested a voluntary commitment product to help smokers quit smoking. The product (CARES) offered smokers a savings account in which they deposit funds for six months, after which they take a urine test for nicotine and cotinine. If they pass, their money is returned; otherwise, their money is forfeited to charity. Eleven percent of smokers offered CARES tookup, and smokers randomly offered CARES were 3 percentage points more likely to pass the 6-month test than the control group. More importantly, this effect persisted in surprise tests at 12 months, indicating that CARES produced lasting smoking cessation.